Body Dissatisfaction dan Pengetahuan Gizi dengan Perilaku Makan pada Mahasiswa Kesehatan - Aslan Saputra Ui; Vivien Novarina A. Kasim; Bergita Dumar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to investigate the relationship between body dissatisfaction, nutritional knowledge, and eating behavior among health students at Gorontalo State University—a cross-sectional study using stratified random sampling that involved 91 health students in their third and fifth semesters. The results showed a significant relationship between body dissatisfaction and eating behavior (p-value = 0.000) and between nutritional knowledge and eating behavior (p-value = 0.000). In conclusion, a significant relationship exists between body dissatisfaction and eating behavior, as well as between nutritional knowledge and eating behavior, among health students. Keywords: Body Dissatisfaction, Eating Disorders, Healthy Students, Nutrition Knowledge, Eating Behavior